The effect of price perception and service quality on user satisfaction with Trans Jatim Corridor II bus services - Cipta Hening Alifiah; Ugy Soebiantoro (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study examines the effects of price perception and service quality on user satisfaction with Trans Jatim Corridor II bus services in Indonesia. A quantitative research design was employed using a survey method, with data collected from 96 users selected through purposive sampling. All research constructs were measured using a five-point Likert scale and analyzed to evaluate the relationships among the variables. The findings indicate that favorable price perceptions and high service quality significantly contribute to user satisfaction, suggesting that both economic and service-related considerations influence passengers' evaluations of public transportation services. The proposed model explains 38.3% of the variance in user satisfaction, indicating that additional factors may also shape users' experiences and perceptions. These results highlight the importance of maintaining affordable fare policies while continuously enhancing service quality to improve customer satisfaction and encourage public transportation usage. The study contributes to the literature on public transportation service management by providing empirical evidence from an emerging transportation system in Indonesia. However, the findings are limited to a single transportation corridor. Future research is recommended to incorporate additional explanatory variables and examine different modes or routes of public transportation to provide a more comprehensive understanding of user satisfaction determinants. Keywords: Price Perception; Service Quality; User Satisfaction